A metaphorical approach to higher education engagement as a liminal and creative free space amid supercomplex and paradoxical dual demands - du Plooy, B. (South African Journal of Higher Education, 2017)
Amid the “continual pandemonium” (Barnett in Smith, 2000:np) of supercomplex competing imperatives, the burning question about the social relevance and impact of universities has become a significant postmillennial concern in higher education. This article explores some of the associated challenges and dynamics and considers ‘higher education engagement’ (broadly defined to mean any interaction between a university and any of its identified communities, both internal and external) as a liminal space for approachability, collaboration and creation, both within and beyond the traditional structures of higher education institutionalisation and disciplinary and methodological silo’s. The article uses three metaphors of space and placement for integrated paradoxical ‘both-and’ thinking in order to conceptualise and articulate the potential of engagement as a liminal creative free space in higher education today. The metaphors are the shifting fulcrum, the agora and heterotopic anxiety. All three resonate with the ideas of paradoxical simultaneous situatedness (localisation) and mobility (globalisation) amid supercomplexity and boundary-challenging liminality, as inherent qualities of the contemporary academic engagement project and the postmillennial higher education landscape with its associated dual demands of globalisation and localisation.